2013
DOI: 10.1142/s1793042113500553
|View full text |Cite
|
Sign up to set email alerts
|

ON THE POLYNOMIAL xd + ax + b OVER 𝔽q AND GAUSSIAN HYPERGEOMETRIC SERIES

Abstract: For d β‰₯ 2, denote by P d (x) the polynomial over Fq given byWe explicitly find the number of solutions in Fq of the polynomial equation P d (x) = 0 in terms of special values of d F dβˆ’1 and dβˆ’1 F dβˆ’2 Gaussian hypergeometric series with characters of orders d and d βˆ’ 1 as parameters. This solves a problem posed by K. Ono (see p. 204 in [Web of Modularity: Arithmetic of the Coefficients of Modular Forms and q-Series, CBMS Regional Conference Series in Mathematics, No. 102 (American Mathematical Society, Providen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It is found that these functions satisfy many summation and transformation formulas analogous to classical hypergeometric series. In a series of papers, many interesting relations have been established between special values of these hypergeometric functions and the number of points on certain algebraic curves over finite fields (see, for examples, [1,2,3,4,5,6,10,9,12,14]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that these functions satisfy many summation and transformation formulas analogous to classical hypergeometric series. In a series of papers, many interesting relations have been established between special values of these hypergeometric functions and the number of points on certain algebraic curves over finite fields (see, for examples, [1,2,3,4,5,6,10,9,12,14]).…”
Section: Introductionmentioning
confidence: 99%
“…Fuselier [6] and Lennon [12] found formulas for the trace of Frobenius endomorphism of a certain family of elliptic curves in terms of Gaussian hypergeometric series containing characters of order 12. In [4], Barman and Kalita found the number of solutions of the polynomial equation x d + ax + b = 0 over a finite field F q in terms of special values of Gaussian hypergeometric series with characters of orders d and d βˆ’ 1 under the condition that q ≑ 1(mod d(d βˆ’ 1)) and d β‰₯ 2. The same authors, in [5], expressed the number of F q -points on a hyperelliptic curve in terms of special values of Gaussian hypergeometric series.…”
Section: Introductionmentioning
confidence: 99%